MODEL KONSEPTUAL PENGEMBANGAN PERIKANAN TONGKOL DAN CAKALANG YANG DIDARATKAN DI KOTA BENGKULU - Silvy Syukhriani; Tri Wiji Nurani; John Haluan (Fakultas Perikanan dan Ilmu Kelautan, 2018)
Bengkulu City is one of the coastal cities that located in the western part of Sumatra island. This city borders directly with the Indian Ocean and had the potential of fisheries, especially for auxis and skipjack. As many as 5.818 tons of auxis fish and 2.031 tons of skipjack fish have been landed every year in PPP Pulau Baai Kota Bengkulu. Despite having abundant fish potency but fisherman can only utilize it equal to 48%. The purpose of this research were to identify the problems that occur in auxis and skipjack fisheries landed in Bengkulu City and create a conceptual model to provide solution related problems in auxis and skipjack fisheries that landed in Bengkulu city. The analysis has been done using Soft System Methodology (SSM). The problems that discovered in auxis and skipjack fisheries are the facilities of PPP Pulau Baai not good enough, DKP can’t give free aid to the right fisherman, Syahbandar can’t do monitoring very well toward fisherman and there isn’t any exist industry of auxis and skipjack in the city. The solution of this research was to improve the facilities of PPP Pulau Baai, the more appropriate target of DKP aid, to activate the processing industry of auxis and skipjack as well as to increase the performance of syahbandar related to the active period of fishing permit.